Race for Applicable Antimicrobial Dental Implant Surfaces to Fight Biofilm-Related Disease: Advancing in Laboratorial Studies vs Stagnation in Clinical Application - De Avila, Erica D. [UNESP]; Nagay, Bruna E.; Pereira, Marta M. A. [UNESP]; Barão, Valentim A. R.; Pavarina, Ana Claudia [UNESP]; Van Den Beucken, Jeroen J. J. P. (American Chemical Society (ACS), 2022)
Across years, potential strategies to fight peri-implantitis have been notoriously explored through the antimicrobial coating implant surfaces capable of interfering with the bacterial adhesion process. However, although experimental studies have significantly advanced, no product has been marketed so far. For science to reach the society, the commercialization of research outcomes is necessary to provide real advancement in the biomedical field. Therefore, the aim of this study was to investigate the challenges involved in the development of antimicrobial dental implant surfaces to fight peri-implantitis, through a systematic search. Research articles reporting antimicrobial dental implant surfaces were identified by searching PubMed, Scopus, Web of Science, The Cochrane Library, Embase, and System of Information on Grey Literature in Europe, between 2008 and 2020. A total of 1778 studies were included for quality assessment and the review. An impressive number of 1655 articles (93,1%) comprised in vitro studies, whereas 123 articles refer to in vivo investigations. From those 123, 102 refer to animal studies and only 21 articles were published on the clinical performance of antibacterial dental implant surfaces. The purpose of animal studies is to test how safe and effective new treatments are before they are tested in people. Therefore, the discrepancy between the number of published studies clearly reveals that preclinical investigations still come up against several challenges to overcome before moving forward to a clinical setting. Additionally, researchers need to recognize that the complex journey from lab to market requires more than a great idea and resources to develop a commercial invention; research teams must possess the skills necessary to commercialize an invention.
Keywords: anti-infective agents; dental implants; surface treatment